Synthesis of [ 18 F]PS13 and Evaluation as a PET Radioligand for Cyclooxygenase-1 in Monkey - Taddei, Carlotta; Morse, Cheryl L; Kim, Min-Jeong; Liow, Jeih-San; Montero Santamaria, Jose; Zhang, Andrea; Manly, Lester S; Zanotti-Fregonara, Paolo; Gladding, Robert L; Zoghbi, Sami S; Innis, Robert B; Pike, Victor W (ACS chemical neuroscience, 2021)
Cyclooxygenase-1 (COX-1) and its isozyme COX-2 are key enzymes in the syntheses of prostanoids. Imaging of COX-1 and COX-2 selective radioligands with positron emission tomography (PET) may clarify how these enzymes are involved in inflammatory conditions and assist in the discovery of improved anti-inflammatory drugs. We have previously labeled the selective high-affinity COX-1 ligand, 1,5-bis(4-methoxyphenyl)-3-(2,2,2-trifluoroethoxy)-1 -1,2,4-triazole (PS13), with carbon-11 ( = 20.4 min). This radioligand ([ C]PS13) has been successful for PET imaging of COX-1 in monkey and human brain and in periphery. [ C]PS13 is being used in clinical investigations. Alternative labeling of PS13 with fluorine-18 ( = 109.8 min) is desirable to provide a longer-lived radioligand in high activity that might be readily distributed among imaging centers. However, labeling of PS13 in its 1,1,1-trifluoroethoxy group is a radiochemical challenge. Here we assess two labeling approaches based on nucleophilic addition of cyclotron-produced [ F]fluoride ion to -difluorovinyl precursors, either to label PS13 in one step or to produce [ F]2,2,2-trifluoroethyl toluenesulfonate for labeling a hydroxyl precursor. From the latter two-step approach, we obtained [ F]PS13 ready for intravenous injection in a decay-corrected radiochemical yield of 7.9% and with a molar activity of up to 7.9 GBq/μmol. PET imaging of monkey brain with [ F]PS13 shows that this radioligand can specifically image and quantify COX-1 without radiodefluorination but with some radioactivity uptake in skull, ascribed to red bone marrow. The development of a new procedure for labeling PS13 with fluorine-18 at a higher molar activity is, however, desirable to suppress occupancy of COX-1 by carrier at baseline.